EFFECT OF TEST-TAKING SKILLS TRAINING COUNSELLING TECHNIQUE ON TEST ANXIETY AMONG SECONDARY SCHOOL STUDENTS IN ILORIN METROPOLIS, NIGERIA - ADEBOYE, Adenike Abiola; M. BUBA; BOLU-STEVE, Foluke Nike; MUSTAPHA, Mulikat L.A.; ONIEMOLA, Roseline Funmilayo (Jurnal Saintifik (Multi Science Journal), 2025)
This study examined the effect of test-taking skills training counselling techniques on test anxiety among secondary school students in Ilorin metropolis, Nigeria. The study aimed to determine the technique's effect on physiological, cognitive, behavioural, and emotional components of test anxiety. The research employed a quasi-experimental design, focusing on 15 SS2 students identified with high test anxiety. Using a Test Taking Anxiety Checklist and Student Test Anxiety Scales, the study measured anxiety levels before and after a 6-week test-taking skills training treatment. Data were analysed using paired sample t-tests to compare pre-test and post-test scores. The findings of this study revealed that test-taking skills training counselling technique had a significant effect on physiological (t = 20.68, p = 0.000), cognitive (t = 16.61, p = 0.000), behavioural (t = 16.55, p = 0.000) and emotional (t = 19.23, p = 0.000) components of test anxiety among secondary school students in Ilorin metropolis. This study therefore concludes that test-taking skills training counselling technique significantly reduced the physiological, cognitive, behavioural and emotional components of test anxiety among secondary school students. Based on this, it was recommended among others that, Professional Counsellors and Psychologists should include the use of test-taking skills and training techniques in secondary school programmes and training to assist the students in learning how to manage their time effectively, have adequate preparation before any test and to read test instructions carefully and attentively